Land of Triumph and Tragedy: Voices of the Italian Fallen Workers: A Century of Italian Immigration to Canada: Immigrants Who Made It and Those Who Perished Trying - Breda, Paola; Toppan, Marino (Verità, 2019)
The Embassy of Italy, the Consulate General of Italy in Toronto and Villa Charities join together with authors Paola Breda and Marino Toppan to present a ground-breaking new history of the Italian-Canadian immigration experience, finally including the previously untold story of the thousands of Italian Fallen Workers who died building this beautiful country — a story that’s destined to become a new piece of Canadian History. Compiled after decades of research by Toppan, this epic new volume includes countless contributions from across the country, from scholars of Italian-Canadian history and the families of the fallen themselves. This ground breaking new book includes profiles of those in the Italian community in Canada who triumphed with incredible successes, those who died in tragic circumstances, as well as in-depth studies on immigration patterns, labour history, socio-adaptive patterns, labour action, strife and hardships experienced, and many more themes in the Italian-Canadian identity. It even coins a new phrase: Canadianità! –Publicity release, May 23, 2019
OCLC: 1129456942